1993
DOI: 10.1017/s003329170002554x
|View full text |Cite
|
Sign up to set email alerts
|

Expressed emotion and schizophrenia: the ontogeny of EE during an 18-month follow-up

Abstract: SynopsisKey relatives of 30 first or early admission psychotic patients (mainly with a diagnosis of schizophrenia) were interviewed (for a second time) 18 months after participating in an initial assessment of expressed emotion (EE). The patients were followed up throughout the interim period, during which time 17 experienced a psychotic relapse. Although there continued to be a negligible association between initial EE rating (established during the index admission) and relapse, a significant association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 25 publications
3
16
0
1
Order By: Relevance
“…Bentsen et al found that anxiety and depression were more prevalent in households where there are high levels of EOI displayed [13]. Stirling et al, looking at a first-episode psychosis sample, contradict many of the previous findings concerning the association of high EE with relapse rates, but are in agreement with a model that takes reactive components of the patient/ illness/relative dynamic into account [14,15]. They found that a very large proportion of their high EE group reached threshold in EOI (14/16) at index but this was greatly reduced by follow up.…”
Section: Emotional Over-involvement and Criticismmentioning
confidence: 73%
“…Bentsen et al found that anxiety and depression were more prevalent in households where there are high levels of EOI displayed [13]. Stirling et al, looking at a first-episode psychosis sample, contradict many of the previous findings concerning the association of high EE with relapse rates, but are in agreement with a model that takes reactive components of the patient/ illness/relative dynamic into account [14,15]. They found that a very large proportion of their high EE group reached threshold in EOI (14/16) at index but this was greatly reduced by follow up.…”
Section: Emotional Over-involvement and Criticismmentioning
confidence: 73%
“…Bentsen et al found that anxiety and depression were more prevalent in households where there are high levels of EOI displayed [13]. Stirling et al , looking at a first‐episode psychosis sample, contradict many of the previous findings concerning the association of high EE with relapse rates, but are in agreement with a model that takes reactive components of the patient/ illness/relative dynamic into account [14,15]. They found that a very large proportion of their high EE group reached threshold in EOI (14/16) at index but this was greatly reduced by follow up.…”
Section: Emotional Over‐involvement and Criticismmentioning
confidence: 78%
“…Recently there has been some controversy about the predictive efficacy of EE in patients experiencing their first episode of psychosis (FEP) with some studies reporting either weak [14][15][16] or no effect of EE on patient relapse [17,18]. Although the majority of studies treated EE as a unitary construct, some attempted to determine the differential predictive power of its two components -CC and EOI [14,18,19]. High EE is usually associated with high levels of CC, which has been found to make a greater contribution to relapse [3,12,[19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%